Answer:
6y³ + 17y² + 22y + 15
Step-by-step explanation:
(2y + 3)(3y² + 4y + 5)
6y³ + 8y² + 10y + 9y² + 12y + 15
6y³ + 8y² + 9y² + 10y + 12y + 15
6y³ + 17y² + 22y + 15
Answer:
y=x-5
Step-by-step explanation:
y=mx+b
-5=0(3)+b
0(3)-5=b
-5=b
y=x-5
Correct me if im wrong
Answer:
-9
0
3
Step-by-step explanation:
-(-2-1)^2
-(1-1)^2
x>2 , so g(x) = 3
By definition, a function is odd if f(-x) = -f(x) for all x in the domain. The answer is choice C
Side note: a function is even if f(-x) = f(x) for all x in the domain
Answer:
33.) = 4
34.) = 2
35.) = 6
36.) = 6
37.) = 91
38.) = 35
39.) = 4
40.) = 28
41.) = 18
42.) = (-6)
Step-by-step explanation:
<h3>33.)</h3>
(10 + 6) ÷ [(9 – 5) × (5 – 4)²]
(16) ÷ (4) × (1)²
16/4 = 4
Thus, The answer is 4
<h3>
34.)</h3>
(3² × 2) ÷ (5 + 8 – 5 + 1)
(9 × 2) ÷ (9)
18/9 = 2
Thus, The answer is 2
<h3>
35.)</h3>
6² ÷ {2 + 5 – [9 – (6 + 2)]}
6² ÷ [2 + 5 – (9 – 8)]
36 ÷ [2 + 5 – (1)]
36 ÷ 7 – 1
36/6 = 6
Thus, The answer is 6
<h3>
36.)</h3>
(3 × 3 × 2) ÷ (4 – 1)
18/3 = 6
Thus, The answer is 6
<h3>
37.)</h3>
4 × 3 × 10 – 4² – (10 + 3)
120 – 16 – 13
120 – 29 = 91
Thus, The answer is 91
<h3>
38.)</h3>
5 × [(22 – 1) × 2] ÷ (8 + 2 – 4)
5 × [(21) × 2] ÷ (6)
5 × 42 ÷ 6
5 × 7 = 35
Thus, The answer is 35
<h3>
39.)</h3>
-2 × 4 ÷ [2 + (-4) – (-4)] – 4
-8 ÷ (2 – 4 + 4) – 4
-8 ÷ 2 – 4
-8/-2 = 8/2 = 4
Thus, The answer is 4
<h3>
40.)</h3>
-4(-1 + 2) × 4 – 2 + (-1)
-4 × (1) × 4 – 2 – 1
(-4) × (-7) = 28
Thus, The answer is 28
<h3>
41.)</h3>
-3 – (-3 × 3) + 6 × 2
-3 – (-9) + 12
-3 + 9 + 12
6 + 12 = 18
Thus, The answer is 18
<h3>
42.)</h3>
6 – {3² + [3 × (-1)²]}
6 – [9 + (3 × 1)]
6 – (9 + 3)
6 – 12 = -6
Thus, The answer is (-6)
<u>-TheUnknownScientist 72</u>